Clinical Predictors of outcome in Isolated Traumatic Acute Subdural Hematoma - Bhattachan, Maya; Niyaf, Ali; Shrestha, Ram K.; Pradhananga, Amit; Sedain, Gopal; Sharma, Mohan R.; Shilpakar, Sushil K. (Nepal Journal of Neuroscience, 2018)
Head injury is the major cause of death in young adult population worldwide with associated high morbidity. The objective of this study is to find out the outcome and factors affecting the outcome in isolated traumatic acute subdural hematoma. All patients with isolated acute subdural hematoma presenting within 24 hours of trauma and admitted over a period of 1 year were included in this study. Patient was classified according to Glasgow Coma Scale(GCS) after resuscitation in the emergency department. The outcome of the patient was recorded according to the Glasgow Outcome Scale at the time of discharge and at 3 months after the trauma in follow-up. Statistical analysis was performed to find the correlation between GCS, papillary changes and radiological finding in the form of midline shift and hematoma volume to dichotomized outcome. Out of 38 patients enrolled in the study, 33 patients had favorable outcome. Surgery was performed in 12 patients out of whom 4 patients had unfavorable outcome. GCS score, papillary changes, midline shift and hematoma volume were found to have significant association with the outcome in isolated traumatic acute subdural hematoma. Clinical parameters and radiological parameters can gauge the outcome in isolated traumatic brain injury.